Psychometric Properties of the Intrapreneurial Self-Capital Scale in Malaysian University Students - Chua Bee Seok; Harris Shah Abd Hamid; Rosnah Ismail (2019)
The Intrapreneurial Self-Capital Scale (ISCS) is a 28-item measure intended to measure individual resources used to manage career and life challenges. The Intrapreneurial Self-Capital (ISC) is a higher order construct composed of seven specific constructs: core self-evaluation, hardiness, resilience, creative self-efficacy, decisiveness, goal mastery, and vigilance. In the new research area of the psychology of sustainability and sustainable development, ISC constitutes a promising core of resources to face the challenges of the 21st century. The aim of the current study was to determine the factor structure and psychometric properties (i.e., reliability and concurrent validity) of a Malaysian version of ISCS among university students. The self-report questionnaire was administered to 1491 university students in Sabah, Malaysia. Confirmatory factor analyses were performed to assess the latent structure of the Malaysian ISCS. The final indices of Goodness of Fit showed satisfactory fit to the data. The Cronbach’s alpha of the Malaysian ISCS is 0.81. The Malaysian ISCS correlates with Career Adaptability r = 0.31 (p < 0.01) and with Life Project Reflexivity r = 0.44 (p < 0.01), thus showing an adequate concurrent validity evidence. The Malaysian ISCS provides a promising research area in psychology (both positive and sustainability). Malaysian parents, teachers and counselors can also use this tool for their development and intervention efforts.